Normative data of sympathetic skin response and RR interval variation in Turkish children - TÜRKDOĞAN, DİLŞAD; AKYÜZ, GÜLSEREN DERYA (My University, 1999)
Sympathetic skin response (SSR) and RR interval variation (RRIV) are used commonly for the assessment of sympathetic and parasympathetic nervous system function, respectively. We determined the normal values of SSR and RRIV in 23 (14 females, nine males) Turkish children aged 5 to 14 (mean 9.86, SD 2.48) years. SSR was recorded on the hands and feet during the electrical stimulation of both median and posterior tibial nerves, respectively. Similar response was elicited on both feet during the stimulation of the right median nerve. RRIV testing was performed during rest on the supine position and deep inspiration at a frequency of 6 times/min. The SSR was elicited in all children. The mean SSR latencies recorded on the feet during the stimulation of median or posterior tibial nerve were significantly more prolonged than those recorded at the hands (P < 0.001). There was no significant difference between the mean latencies of SSR recorded at the ipsilateral and contralateral palms or soles. The mean latencies recorded at the sole during stimulation of the median nerve were not significantly different compared to those that recorded at the sole during the posterior tibial nerve (P > 0.05). The SSR amplitudes were not assessed because of great variability and rapid habituation. The mean RRIV (46.54+/-11.29%) during deep breathing was significantly increased as compared to that (35.90+/-10.63%) during rest (P < 0.003). As a result, SSR and RRIV are preferred non-invasive tests for evaluation of autonomic nervous system in children. The SSR is useful and reliable if it is obtained in the optimum technical conditions. Further research is necessary to establish strict criteria for abnormality.
Keywords: Female; Humans; Adolescent; Male; Skin; Child; Child, Preschool; Reference Values; Reaction Time; Heart Rate; Electric Stimulation; Foot; Hand; Median Nerve; Sympathetic Nervous System; Tibial Nerve